2018
DOI: 10.21608/ejmm.2018.285751
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Toxin-Antitoxin System in Acinetobacter baumannii Isolated from Patients at Zagazig University Hospitals

Abstract: Increased resistance to antibiotics among Acinetobacter baumannii (A. baumannii) isolates is a rising problem, and new alternatives should be provided to overcome this problem. Toxin-Antitoxin system (TA) is considered a promising essential target for antimicrobial drugs. Objective: To detect the prevalence of toxin-antitoxin system in A. baumannii isolated from patients at Zagazig University Hospitals. Methodology: Following isolation, oxidase test and API20NE were used to identify A. baumannii, antibiotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…According to our results, the highest rate of A. baumannii isolates was collected from the trachea specimens (31 isolates; 51.7%), which is consistent with the findings reported in a study by Alkasaby and colleagues [42]. Furthermore, as reported by Maghraby et al, the majority of A. baumannii isolates were related to chest infection specimens [26]. However, Al Mobarak et al reported some contradicting results in this regard as they reported that A. baumannii isolates were mainly isolated from wounds, respiratory secretions, urine, and blood [43].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…According to our results, the highest rate of A. baumannii isolates was collected from the trachea specimens (31 isolates; 51.7%), which is consistent with the findings reported in a study by Alkasaby and colleagues [42]. Furthermore, as reported by Maghraby et al, the majority of A. baumannii isolates were related to chest infection specimens [26]. However, Al Mobarak et al reported some contradicting results in this regard as they reported that A. baumannii isolates were mainly isolated from wounds, respiratory secretions, urine, and blood [43].…”
Section: Discussionsupporting
confidence: 93%
“…To our knowledge, only a few studies have investigated the prevalence and functionality of the TA system genes in bacterial isolates. According to a similar study on 27 A. baumannii isolates, 62.9% had the mazEF gene, 81.5% had the relBE gene, and 29.6% had the higBA gene [ 26 ]. As reported by Ghafourian et al, the chromosomal DNA of all of the A. baumannii isolates (100%) were positive for mazEF , and that relBE was found in the chromosomal DNA of only 88.2% of the bacterial isolates whereas higBA was the least prevalent gene (4.7%) in the bacterial isolates [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation